Charge‐Carrier Dynamics and Mobilities in Formamidinium Lead Mixed‐Halide Perovskites. (24th September 2015) - Rehman, Waqaas; Milot, Rebecca L.; Eperon, Giles E.; Wehrenfennig, Christian; Boland, Jessica L.; Snaith, Henry J.; Johnston, Michael B.; Herz, Laura M.
Abstract : The mixed‐halide perovskite FAPb(Br y I1– y )3 is attractive for color‐tunable and tandem solar cells. Bimolecular and Auger charge‐carrier recombination rate constants strongly correlate with the Br content, y, suggesting a link with electronic structure. FAPbBr3 and FAPbI3 exhibit charge‐carrier mobilities of 14 and 27 cm 2 V −1 s −1 and diffusion lengths exceeding 1 μm, while mobilities across the mixed Br/I system depend on crystalline phase disorder.